Dissection of binding of trypsin to its natural inhibitor Gensenoside-Rg1 using spectroscopic methods and molecular modeling. Issue 15 (13th October 2019) - Lin, Jialiang; Xu, Yang; Wang, Yuhan; Huang, Songyang; Li, Junwei; Meti, Manjunath D.; Xu, Xu; Hu, Zhangli; Liu, Johnson; He, Zhendan; Xu, Hong
Abstract: The interaction of trypsin with Gensenoside-Rg1 (G-Rg1) was studied using fluorescence, ultraviolet–visible (UV–vis), and circular dichroism (CD) spectroscopies along with enzyme activity assay and molecular docking. The enzyme activity assays showed that G-Rg1 inhibited the activity of trypsin effectively. The fluorescence experiments indicated that a complex of G-Rg1–trypsin was formed and that the fluorescence of trypsin was quenched by G-Rg1 via a mixed-quenching mechanism (both static and dynamic quenching). The thermodynamic analysis suggested that hydrophobic interaction and hydrogen bond were the major forces between G-Rg1 and trypsin. According to the theory of Förster's non-radiation energy transfer, the binding distance between trypsin and G-Rg1 was calculated to be 2.01 nm, which implies that energy transfer occurred within the complex. The experimental results obtained from UV–vis absorption spectra, synchronous fluorescence spectra, and CD spectra indicated that G-Rg1 was mainly located on tryptophan moiety and that the interaction between G-Rg1 and trypsin led to conformational changes of trypsin with some α-helix and unordered coil structures being transformed into β-sheet structures. In addition, docking results supported the above experimental findings and suggested the possible binding location of G-Rg1 on trypsin along with the possible hydrogen bonds and hydrophobic interactions between G-Rg1 and trypsin. The experimental results from this study should be useful to minimize the antinutritional effects and make full use of Genseng extracts in the food industry and also be helpful to the design of the drugs for the diseases related to overexpression of trypsin. Communicated by Ramaswamy H. Sarma